\(\left(x-2\right)\left(x+2\right)-\left(2x+1\right)^2=x\left(2-3x\right)\)
\(\Leftrightarrow x^2-4-4x^2-4x-1=2x-3x^2\)
\(\Leftrightarrow-3x^2+3x^2-4x-2x=1+4\)
\(\Leftrightarrow-6x=5\Leftrightarrow x=-\dfrac{5}{6}\)
Vậy......
(x-2)(x+2)-(2x+1)2 =x(2-3x)
\(\Leftrightarrow x^2-4-4x^2-4x-1=2x-3x^2\)
\(\Leftrightarrow x^2-4-4x^2-4x-1-2x+3x^2=0\)
\(\Leftrightarrow-6x-5=0\)
\(\Leftrightarrow x=\dfrac{-5}{6}\)
\(\Rightarrow S=\left\{\dfrac{-5}{6}\right\}\)
<=> \(x^2-4-4x^2-4x-1=2x-3x^2\)
<=> \(x^2-4x^2+3x^2-4x-2x=4+1\)
<=> \(-6x=5\)
<=> \(x=-\dfrac{5}{6}\)
(x-2)(x+2)-(2x+1)2=x(2-3x)
\(x^2-4-4x^2-4x-1=2x-3x^2\)
\(x^2-4-4x^2-4x-1-2x+3x^2=20\)
\(-6x-5=0\)
\(x=\dfrac{-5}{6}\)